The Impact of Extreme Situations on Students with Dyslexia: Lessons from the Pandemic - Ana Isabel González Contreras; David Pérez Jorge; Elena Honorio González; Isabel Alonso Rodríguez (Journal of Language and Education)
Background. The state of emergency triggered by Covid-19 has significantly impacted various sectors, with education being one of the most affected. This qualitative study explores the psychosocial and educational repercussions for students with Specific Learning Difficulties (SLD), focusing mainly on those with dyslexia and their families. That is, understand how dyslexic students and their families have experienced their confinement and what psychosocial and educational consequences have derived from this situation.